How Inclusive Classroom Practices Foster Interpersonal Intelligence among Young Children: A Case Study in Early Childhood Education - Fadlilah, Azizah Nurul; Azhari, Supian; Masfiah, Saidah (JOYCED: Journal of Early Childhood Education, 2026)
Purpose — This study aims to analyze the implementation of inclusive classes in developing interpersonal intelligence of early childhood in Al-Huda Kindergarten. The focus of the research is directed at the inclusive learning process, social interactions between regular children and children with special needs, and the role of teachers in supporting children's interpersonal development. Design/methods/approach — This research used a qualitative approach with a descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, classroom teachers, assistant teachers, and early childhood students. Data analysis was conducted using an interactive model through the stages of data reduction, data presentation, and drawing conclusions. Findings — Research results show that implementing inclusive classes can improve early childhood interpersonal intelligence through cooperative play, collaborative learning, and positive social interactions. Children demonstrate development in their ability to work together, social communication, empathy, and tolerance towards peers. Teachers play a crucial role in creating an inclusive learning environment and supporting the involvement of all children in learning activities. Research implications/limitations — This study suggests that inclusive learning can be an effective strategy for developing interpersonal intelligence in early childhood. However, the study was limited to one early childhood education institution, so the results cannot be generalized widely. Originality/value — This research contributes to the development of inclusive early childhood education studies by emphasizing the importance of social interaction in inclusive classes as a means of developing children's interpersonal intelligence.